2018
DOI: 10.1007/s00520-018-4076-6
|View full text |Cite
|
Sign up to set email alerts
|

Treatment toxicities and their impact on oral intake following non-surgical management for head and neck cancer: a 3-year longitudinal study

Abstract: The dysphagia and associated toxicities HNC patients experience are chronic in nature. Rehabilitation should include mealtime strategies and support with adjusting to the changing presence and impact of toxicities on oral intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 34 publications
1
65
0
Order By: Relevance
“…Patients' perception of dry mouth has been examined in the primary CRT population, often using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck–35 (EORTC QLQ‐H&N35) patient‐rated QOL scale. Studies have typically examined outcomes within the first 6 to 12 months; however, studies have shown complaints of xerostomia up to 3 years following radiotherapy (RT) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' perception of dry mouth has been examined in the primary CRT population, often using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Head and Neck–35 (EORTC QLQ‐H&N35) patient‐rated QOL scale. Studies have typically examined outcomes within the first 6 to 12 months; however, studies have shown complaints of xerostomia up to 3 years following radiotherapy (RT) .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20][21] In addition, this test has been performed in conjunction with a battery of other vocal tract assessments, as it can easily be completed during a clinic visit. [15][16][17][18][19][20] Patients' perception of dry mouth has been examined in the primary CRT population, 14,15,[20][21][22][23] 24 patient-rated QOL scale. Studies have typically examined outcomes within the first 6 to 12 months 15,20,25 ; however, studies have shown complaints of xerostomia up to 3 years following radiotherapy (RT).…”
Section: Introductionmentioning
confidence: 99%
“…Xerostomia is an unpleasant symptom which may negatively interfere with many aspects of daily life: oral pain, difficult meal selection (in terms of both nutritional value and food consistency), time required to finish a meal, quality of sleep, and speech difficulties. There has been a shift away from clinician‐rated toxicity to patient‐focused reporting of symptoms to improve understanding of the patient experience as it has been alleged that observer‐rated scores have underestimated the severity of symptoms . Furthermore, it has been reported that saliva volume does not always correlate with subjective symptoms of xerostomia .…”
Section: Discussionmentioning
confidence: 99%
“…There has been a shift away from clinician-rated toxicity to patientfocused reporting of symptoms to improve understanding of the patient experience as it has been alleged that observer-rated scores have underestimated the severity of symptoms. 18,19 Furthermore, it has been reported that saliva volume does not always correlate with subjective symptoms of xerostomia. 20 This study still included objective saliva volume as an outcome as purely subjective measurements may not be accepted by some for inclusion in meta-analysis studies.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation associated dysphagia can also result from the acute toxicities associated with treatment including but not limited to: mucositis, pain, xerostomia, thick saliva, dysgeusia, nausea, fatigue, altered sensation, and fibrotic tissue changes within the head and neck region (Barnhart et al, 2018;Cartmill, Cornwell, Ward, Davidson, & Porceddu, 2013;Chera et al, 2014;Hj Wu, 2009;Holländer-Mieritz et al, 2019;Logemann et al, 2008;Siddiqui & Movsas, 2017). These related toxicities will be discussed in detail in the below sections as they relate to acute and late toxicity.…”
Section: Dysphagia and Related Toxicitiesmentioning
confidence: 99%